Quraish Shihab's Thoughts on The Relationship Between Politics and Religion - Marzuqoh, Nur Auliya; Patriotik, Anisa Bangkit; Shidiqi, Rosyid Ash; Hasanah, Sabilatul; Bainallail, Raya; Rahmadani, Mutiara Fitri; Tafarod, Khusna (TATHO: International Journal of Islamic Thought and Sciences, 2025)
This study examines the relationship between religion and politics and its relevance to the current socio-political conditions in Indonesia based on the views of Quraish Shihab as a moderate Muslim figure. The objective of this qualitative research is to conduct a content observation study of YouTube, through a content analysis approach and literature study. This study concludes that Quraish Shihab views religion and politics as two interrelated things, with Islamic values as the moral foundation of politics. He rejects the exclusive politicization of religion and emphasizes the importance of justice, welfare, and common interests in a pluralistic state. This study contributes to contemporary Islamic thought by examining the relationship between religion and politics through thematic interpretation in affirming the integration of Islamic values and state practices in a pluralistic society.